Recent advances in understanding of enterobacterial common antigen synthesis and regulation - Haley C. Bennett; Angela M. Mitchell (Open Biology)
Antibiotic resistance has become one of the most significant global health threats, with nearly three million antibiotic-resistant infections occurring per year in the United States alone. This problem is especially acute in Gram-negative bacteria, which possess an outer membrane (OM) that surrounds the aqueous periplasm and cytoplasmic membrane and acts as a permeability barrier capable of excluding many antibiotics. The OM of Enterobacterales also contains a highly conserved, invariant carbohydrate-derived moiety known as enterobacterial common antigen (ECA), which has been shown to play a significant role in this membrane permeability barrier. Although ECA was first discovered in the 1960s, its precise function and regulation remain largely mysterious. Here, we highlight recent studies that have advanced our understanding of the structure, biosynthesis, regulation and potential functions of ECA. We also review new insights into the complex interactions of the cell envelope biosynthesis pathways which may also play a role in surface antigen biosynthesis.